Anomalous formation of trihydrogen cations from water on nanoparticles - Alghabra, M. Said; Ali, Rami; Kim, Vyacheslav; Iqbal, Mazhar; Rosenberger, Philipp; Mitra, Sambit; Dagar, Ritika; Rupp, Philipp; Bergues, Boris; Mathur, Deepak; Kling, Matthias F.; Alnaser, Ali S. (Nature Communications, 2021)
Regarded as the most important ion in interstellar chemistry, the trihydrogen cation, H3+, plays a vital role in the formation of water and many complex organic molecules believed to be responsible for life in our universe. Apart from traditional plasma discharges, recent laboratory studies have focused on forming the trihydrogen cation from large organic molecules during their interactions with intense radiation and charged particles. In contrast, we present results on forming H3+ from bimolecular reactions that involve only an inorganic molecule, namely water, without the presence of any organic molecules to facilitate its formation. This generation of H3+ is enabled by “engineering” a suitable reaction environment comprising water-covered silica nanoparticles exposed to intense, femtosecond laser pulses. Similar, naturally-occurring, environments might exist in astrophysical settings where hydrated nanometer-sized dust particles are impacted by cosmic rays of charged particles or solar wind ions. Our results are a clear manifestation of how aerosolized nanoparticles in intense femtosecond laser fields can serve as a catalysts that enable exotic molecular entities to be produced via non-traditional routes.
CRIS-Team Scopus Importer:2023-04-20